Evaluation of the nonmarket value of livestock and poultry feces returning to farmland utilization using CVM in Heilongjiang, China - Shang, Jiajie; Xie, Yongtao; Guo, Lifeng; Fan, Jinxia; Liu, Hongxin (International Journal of Agricultural and Biological Engineering, 2023)
Aiming at a series of hot issues and topics, such as resource waste, environmental pollution, and Mollisol protection, related to the arbitrary discharge of livestock and poultry feces, livestock and poultry feces are taken as the research object, a questionnaire survey was conducted to investigate residents’ cognition and willingness to pay (WTP) for the nonmarket value of livestock and poultry feces returning to farmland in Heilongjiang Province, China. The contingent valuation method (CVM) was used for the correlation analysis of WTP and socioeconomic characteristics, and correlation analysis of payment mode and socioeconomic characteristics. Meanwhile, the factors influencing WTP and payment mode were analyzed. The results show that the majority of the respondents are aware of the harmfulness of the arbitrary discharge of livestock and poultry feces and the importance of its nonmarket regeneration value. Approximately 90.09% of respondents were willing to pay for the return of livestock and poultry feces to fields. In 2020, the total value of WTP of livestock and poultry feces returning to farmland in Heilongjiang Province was 4.65 billion CNY, equivalent to 1.32% of the total agricultural production of Heilongjiang Province in the same year. And the nonmarket value of livestock and poultry feces is estimated to be 1456.69 CNY/t. The annual average WTP of rural and urban households is 286.42 CNY and 422.90 CNY per household, accounting for 0.46% and 0.52% of the average annual income of households, respectively. Therefore, the return of livestock and poultry feces to farmland utilization has a high nonmarket value. The analysis shows that the average annual household income is a significant factor in WTP, and the registered permanent residence type and the average annual household income are significant factors in payment mode. The research results should provide a scientific and theoretical basis for the government’s policy and decision-making on the return of livestock and poultry feces to farmland. Keywords: nonmarket value, livestock and poultry feces, farmland utilization, CVM, WTP DOI: 10.25165/j.ijabe.20231602.7588 Citation: Shang J J, Xie Y T, Guo L F, Fan J X, Liu H X. Evaluation of the nonmarket value of livestock and poultry feces returning to farmland utilization using CVM in Heilongjiang, China. Int J Agric & Biol Eng, 2023; 16(2): 48-56.